IMMUNOMODULATORY ACTIVITY OF FLURBIPROFEN IN MICE - M. B. Nasim; A. Javeed; M. Ashraf; M. O. Omer; A. Bukhsh; A. Sharif; K. Amir (Journal of Animal and Plant Sciences, 2016)
Flurbiprofen is a propanoic acid derivative which is widely used and has well-known anti-inflammatory and analgesic effects. Many new studies have emerged which display the immuno-pharmacological behavior of NSAIDs. The immunomodulatory activity of flurbiprofen was evaluated in this work by using immunological experimental models like cyclophosphamide induced neutropenia assay, delayed type hypersensitivity assay, haemagglutination assay and mice lethality test. Cyclophosphamide induced neutropenia and delayed type hypersensitivity assays were performed to evaluate cell mediated immunity while the other two models were used to evaluate the effect of flurbiprofen on humoral immunity. Flurbiprofen was administered intraperitoneally into swiss albino mice at the doses of 5 mg/kg and 10 mg/kg body weight of mice. The drug in both doses decreased the circulating antibodies, and did not prevent the mortality induced by a deadly bovine Pasteurella multocida, evaluated by hemagglutination antibody titer and mice lethality test respectively. Similarly, flurbiprofen did not show any significant effect on T cells. The decrease in skin thickness in delayed type hypersensitivity assay indicated the inability of flurbiprofen to stimulate the T cells. WBCs and neutrophil count reduction showed lack of flurbiprofen effectiveness in preventing cyclophosphamide induced neutropenia. In conclusion, flurbiprofen decreased both humoral and cell mediated immunity in mice.
Keywords: Humoral immunity; Flurbiprofen; Cellular Immunity; Cyclophosphamide; Pasturella multocida